Aktivitas Ekstrak Daun Jarak Pagar (Jatropha curcas L.) terhadap Pertumbuhan Bakteri Salmonella typhimurium dan Staphylococcus aureus - Rahayu, Kun Mardiwati; Parameswari, Shahnaz Kintan; Noriko, Nita (Universitas Al Azhar Indonesia, 2025)
Most infectious diseases occur in the digestive tract caused by Salmonella typhimurium, while in the respiratory tract caused by Staphylococcus aureus. Continuous use of antibiotics as a treatment for bacterial diseases can result in resistance, therefore it needs to be balanced with the discovery of herbal medicines. Jatropha curcas is thought to have the ability to inhibit the growth of gram-positive and gram-negative bacteria. The purpose of this study was to obtain data and information on the antibacterial activity of Jatropha curcas leaf extract. This study used the paper disc diffusion method with 6 treatments and 3 repetitions. The treatments used were positive control (chloramphenicol), negative control (DMSO), and concentration of Jatropha curcas leaf extract of 10%; 20%; 40% and 80%. The results showed that Jatropha curcas leaf extract at concentrations of 10%, 20%, 40% and 80% had an effect on the growth of Salmonella typhimurium with the average inhibition zone obtained being 9.78; 9.19; 11.95; and 16.88 mm. At concentrations of 10%, 20%, 40% and 80%, it has an effect on the growth of Staphylococcus aureus with the average inhibition zone results obtained being 13.23; 14.83; 16.01; and 18.03 mm.Keywords – Jatropha Leaf Extract, Salmonella Typhimurium, Staphylococcus Aureus.